1981
DOI: 10.2337/diab.30.6.535
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plasma Glucose Concentration on Glucose Utilization and Glucose Clearance in Normal Man

Abstract: Glucose clearance (glucose utilization divided by plasma glucose) is commonly used to assess glucose utilization under conditions in which plasma glucose concentrations vary. The validity of this practice requires that glucose clearance itself be independent of plasma glucose concentration. The present studies were, therefore, undertaken to determine the relationship between glucose clearance and plasma glucose concentration in man. Using the glucose clamp technique, rates of glucose utilization (measured isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(26 citation statements)
references
References 9 publications
3
23
0
Order By: Relevance
“…This is consistent with our previous work demonstrating that acute supplementation of glucose does not lead to an increase in circulating glucose levels [18]. This is also consistent with other work demonstrating that low circulating blood glucose leads to rapid blood glucose clearance in humans after a bolus of glucose [28], and ketone bodies are rapidly cleared from plasma in rats under calorie-restricted conditions [29]. Rapid blood glucose clearance is associated with increased cerebral glucose utilization and seizures [18, 30].…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with our previous work demonstrating that acute supplementation of glucose does not lead to an increase in circulating glucose levels [18]. This is also consistent with other work demonstrating that low circulating blood glucose leads to rapid blood glucose clearance in humans after a bolus of glucose [28], and ketone bodies are rapidly cleared from plasma in rats under calorie-restricted conditions [29]. Rapid blood glucose clearance is associated with increased cerebral glucose utilization and seizures [18, 30].…”
Section: Discussionsupporting
confidence: 93%
“…This nonlinear relationship between transport and concentration has been previously reported for FFA (13) and also applies to glucose (27). We found that oleate clearance is higher during intravenous niacin infusion compared with saline infusion in healthy volunteers; this occurs in the context of a marked decrease in oleate concentration and no change in insulin concentrations (R.H.N.…”
Section: Discussionsupporting
confidence: 77%
“…To define the efficiency with which this glucose was metabolized, the metabolic clearance rate (MCR) of glucose was calculated by dividing the amount of glucose metabolized (M) by the plasma glucose concentration. Although this calculation may not be valid when the insulin infusion rate and steady‐state insulin levels are lower than in this study, 12, 13 its use has been validated under the conditions we employed 14, 15 …”
Section: Methodsmentioning
confidence: 99%